Aloe Vera Agribusiness Development Sustainability Analysis in Bogor Regency - Sulhajji Jompa; Rizal Syarief; Surjono Hadi Sutjahjo; Anton Yulianto (Hasanuddin University, 2021)
As a suburban area, Bogor Regency faces complex problems in the development of the aloe vera agribusiness. Land use conflicts, unemployment problems due to the Covid-19 pandemic, financial support and market access, post-harvest handling, and institutional support put the sustainability status of this commodity agribusiness into question. This research was conducted to assess the sustainability of aloe vera agribusiness development in Bogor Regency. Analysis of the sustainability status uses the MDS (multidimensional scaling) method, using four dimensions, namely: social, economic, institutional, and environmental. MDS analysis utilizes the Rapid Appraisal for Fisheries (RAPFISH) software. The research was conducted in five sub-districts in Bogor Regency, namely Kemang, Tajur Halang, Rancabungur, Ciampea, and Mount Sindur Districts. The results showed that, in general, aloe vera agribusiness in Bogor Regency has a sustainable status of: